A Novel Approach for Evaluating GIC Impacts in the Swedish Power Grid - L. Rosenqvist; A. Johlander; S. Molenkamp; A. P. Dimmock; J. Setréus; V. Lanabere (Space Weather)
Abstract The dynamic behavior of the Sun and its interaction with the magnetosphere and ionosphere can cause rapid variations in the geomagnetic field at ground level, geomagnetically induced currents (GICs) flowing through long grounded conductors. The most severe impacts of GICs include power grid disruptions and can, in extreme cases, cause widespread power blackouts. Thus, it is important to investigate GICs to understand the impacts, improve predictions, and develop appropriate mitigation measures. A comprehensive list of disturbances reported in the Swedish power grid between 1999 and June 2024 is evaluated in collaboration with the Swedish authority responsible for the electrical transmission system, Svenska Kraftnät. Using a regional modeling capability of geoelectric fields in Sweden and a simplified yet representative equivalent circuit model of the national power grid, the resulting GICs in the earthing nodes of the network are calculated. The calculated GICs are cross‐correlated with the power grid disturbances to determine which events may have been caused by space weather. By disregarding events with known causes (lightning, fallen trees, equipment failures, etc.), events associated with significant voltage deviations are identified as likely GIC‐related disturbances. While it is not possible to pinpoint the exact location of the impact in the grid or the absolute magnitude of the GICs, both dependent on the accuracy of the grid circuit model, the maximum modeled GICs overlap with several previously uncategorized disturbances. These results highlight the value of the unique collaboration between the scientific community and the power grid operator in Sweden.